3D-printed titanium dioxide-reinforced calcium silicate composite scaffold promotes efficient bone defect repair through activation of osteogenic and angiogenic differentiation - Zhiqiang Huang; Xinyi Wang; Zhaowenbin Zhang; Bin Yu; Suqi Wang; Xiaoting Chen; Yi Zhang; Jin Yang; Zhen Zeng; Zhihong Dong (Materials & Design)
Addressing the challenges of insufficient mechanical strength, high fragility, and rapid degradation in calcium silicate (CS) 3D-printed bone regeneration scaffolds and acknowledging the necessity to enhance performance of CS in bone and vascular regeneration, this study innovatively presents a titanium dioxide (TiO2) reinforcement strategy. This strategy has led to the successful creation of a novel TiO2-reinforced CS composite 3D-printed bone regeneration scaffold (CST). By forming a solid solution during the sintering process between TiO2 and CS, a marked improvement in the overall material strength is attained. Additionally, by leveraging the synergistic pro-regenerative effects of bioactive Si ions Ti ions, the capacity of CST for bone and vascular regeneration is significantly enhanced. In comparison to the pure CS scaffold, the CST scaffold, when reinforced with TiO2, not only maintains a similar porosity but also exhibits enhanced compressive strength, a slower degradation rate, and notably increased osteogenic induction and angiogenic activity. In vivo studies employing a cranial bone defect model have confirmed that the CST scaffold can substantially promote vascular neogenesis and bone regeneration, fully demonstrating its wide-ranging application potential in the field of bone defect treatment.